Предмет: Алгебра,
автор: msonyka
. Представьте выражение (3х – 7y) (-2x – 3y) - (3x+y) (-4х + 5y)
в виде МНОГОЧлена стандартного вида.
ПОЖАЛУЙСТА
Ответы
Автор ответа:
3
Ответ:
(3x-7y)(-2x-3y)-(3x+y)(-4x+5y)= - 6x²- 9xy+14xy+21y²-(-12x²+15xy-4xy+5y²)=15xy+21y²+12x²-15xy+4xy-5y²=12x²+4xy+16y²
Автор ответа:
0
Ответ:(3x-7y)(-2x-3y)-(3x+y)(-4x+5y)= - 6x²- 9xy+14xy+21y²-(-12x²+15xy-4xy+5y²)=15xy+21y²+12x²-15xy+4xy-5y²=12x²+4xy+16y²
Объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: Kulcka
Предмет: Русский язык,
автор: audamir
Предмет: Другие предметы,
автор: SHAPOVALOVA56789
Предмет: История,
автор: Parkrill
Предмет: Математика,
автор: opagangamstile